2011
DOI: 10.1097/jac.0b013e3181ff7080
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Medical Homes in the United States

Abstract: The concept of a medical home is receiving increased attention as a potential means to improve care and reduce costs. This study describes the characteristics and capabilities of practices that have achieved recognition of National Committee for Quality Assurance as a "patient-centered medical home" (PCMH). Both small and large practices demonstrate capabilities related to the goals of PCMH of accessible, coordinated, and patient-centered care; however, practices affiliated with larger organizations achieve hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 15 publications
0
30
1
Order By: Relevance
“…Thus, it provides important insights for the majority of primary care practices in the U.S. 10 In contrast to previous reports, [11][12][13][14] we found that practice size posed no disadvantage in making the transition to a PCMH over time. However, the key to success was clearly the provision of support in the form of revised payment, on-site practice redesign expertise, and on-site care management personnel.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, it provides important insights for the majority of primary care practices in the U.S. 10 In contrast to previous reports, [11][12][13][14] we found that practice size posed no disadvantage in making the transition to a PCMH over time. However, the key to success was clearly the provision of support in the form of revised payment, on-site practice redesign expertise, and on-site care management personnel.…”
Section: Discussioncontrasting
confidence: 56%
“…10 There is growing concern about the capacity of small practices to make the PCMH transition. [11][12][13][14] Early evaluation reports on successful transitions, while informative, 5,7,8,15 lack relevance for small practices. As others have reported, 11 smaller practices lack many of the characteristics associated with successful change in some demonstrations, such as a history of successful change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Advocates of medical homes often describe them as uniquely and markedly different from traditional practices, in both process and outcomes. 5 As a result, medical homes are often compared with non-medical homes.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Because of the level of investment required, one strategy for encouraging widespread adoption of the PCMH model has been to offer practices formal recognition as a PCMH by the National Committee for Quality Assurance (NCQA). 15 This recognition allows practices to publicly promote their status, which may bolster their reputation in the community and, in some cases, garner enhanced reimbursements from payers. To apply for recognition, however, practice staff and administrators need to understand the PCMH standards and application requirements.…”
mentioning
confidence: 99%